Dirty Hands: Government Torture and Terrorism. (July 2017) - Daxecker, Ursula
Existing research suggests that the use of harsh repression can exacerbate the incidence and duration of terrorism. Micro- and macro-level analyses have shown that coercive government responses to terrorism can radicalize sympathizers, increase recruitment, and undermine community support for counterterrorism policies, leading to backlash and increased terrorist activity. Focusing on torture techniques, this article aims to establish mechanisms implicit in the backlash hypothesis. These arguments imply that information about government transgressions is available to potential group sympathizers, but have not examined whether and how variation in the visibility of different torture techniques affects the likelihood of backlash. Scarring torture, a technique that is both more visible and less plausibly deniable than other forms of torture, is expected to produce higher volumes of terrorism. Using disaggregated data on allegations of torture from the Ill-Treatment and Torture project for 1995 to 2005, the analysis shows that scarring torture is consistently associated with increases in terrorism, whereas stealth torture has no statistically discernable effect on terrorism.